Consummatory successive negative contrast in rats: Assessment through orofacial taste reactivity responses - Cuenya, Lucas; Bura, Stefana; Serafini, Matías; López, Matías (Learning and motivation, 2018)
•The effect of successive negative contrast on taste palatability was examined in rats.•A successive negative contrast procedure reduced appetitive taste reactivity responses.•Incentive devaluation reduced intake and the hedonic value of the expected reward. Rats exposed to a downshift from a large reward (32% sucrose) to a small reward (4% sucrose) show an abrupt and transient reduction in consumption in comparison with animals that are always exposed to the small reward. This effect is called consummatory Successive Negative Contrast (cSNC) and involves negative affective consequences that lead to an aversive emotional, cognitive and behavioral state of frustration. There are few previous works that have investigated the hedonic alterations that undergo an unexpected incentive devaluation. The hedonic impact of fluids can be reliably assessed by examining the orofacial reactions of acceptance and rejection in the taste reactivity (TR) test. This study addressed in male adult Wistar rats the hedonic impact of incentive devaluation in an adapted cSNC protocol. Specifically, the orofacial responses to a sucrose solution infused into the oral cavity were measured. It was observed that animals exposed to reward devaluation, from a 32% to a 4% sucrose solution, showed a decrease in the duration of appetitive responses (tongue protrusions, mouth movements, paw licks) as compared with subjects which only experienced the low concentration of sucrose. The results are consistent with the hypothesis that incentive devaluation in a cSNC not only results in reduced intake, but also in a reduction in the hedonic value or palatability of the devalued reward.